THE POTENCY OF INDONESIA’S POMEGRANATE PEEL ETHANOL EXTRACT (PUNICA GRANATUM LINN.) AS ANTI-INFLAMMATORY AGENT IN MICE COLON INDUCED BY DEXTRAN SODIUM SULFATE: FOCUS ON CYCLOOXYGENASE-2 AND INOS EXPRESSIONS - Kusmardi, Kusmardi; Hermanto, Dony; Estuningytas, Ari; Tedjo, Aryo; Priosoeryanto, Bambang P (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Inflammatory disease occurs in the mucosal of the colon, or ulcerative colitis (UC) is one of subtypes of inflammatory bowel disease. The numerous of drug side effects for treatment of colitis give rise to use medicinal herbs as alternative therapies. Pomegranate peel extract has been used for the treatment of pain and inflammatory conditions. This study aimed to investigate the anti-inflammatory effects of pomegranate peel ethanol extract on mice colon through inflammation pathway which reduce inflammation score in mice model of chronic inflammation induced by dextran sodium sulfate (DSS). Methods: Thirty Swiss Webster mice divided randomly into 6 groups: Normal, aspirin 43 mg/kg/d (ASP), ellagic acid 26 mg/kg/d (ELG), DSS 2%b/v (DSS), pomegranate peel ethanol extract 240 mg/kg/d (DOSES-1), and 480 mg/kg/d (DOSES-2). All groups were given DSS 2% over 3 cycles except normal group (where each cycle in the DSS group consisted of 2% DSS in drinking water for 7 days, followed by a 7-day interval with normal drinking water). At the end of the experiment, colon samples were washed with water then buffered neutral formalin 10% fixed and paraffin embedded for histological analysis. Results: DOSES-1 and DOSES-2 were significantly reduced inflammation score in colon mice induced by DSS (p<0.05), mean score 2.01 and 2.02. Expression of cyclooxygenase (COX-2) was significantly decreased (p<0.05), mean score 27.48 and 17.77. Expression of iNOS was also significantly decreased (p<0.05), mean score 54.01 and 36.69. There were no significant differences between DOSES-1 and DOSES-2 groups with ASP and ELG group (p>0.05). Conclusion: Pomegranate peel ethanol extract has an anti-inflammatory agent by reduces inflammation score, inhibiting COX-2 and iNOS expression on mice colon by DSS induced. Furthermore, pomegranate peel ethanol extract has equivalent effectiveness with aspirin and pure ellagic acid.